2020
DOI: 10.1136/bmjopen-2019-034179
|View full text |Cite
|
Sign up to set email alerts
|

Repeat testing without having ‘the talk’ is not meaningful’—healthcare providers’ perceptions on finding a balance between Chlamydia trachomatis testing and primary prevention strategies. A qualitative study in Stockholm, Sweden

Abstract: ObjectivesChlamydia trachomatis is a public health problem. Widespread testing and re-testing after a sexually transmitted infection (STI) is recommended to contain the epidemic and has been adopted by many countries. A recent study in Stockholm found that serial testing was used as a substitute for condom use by youth presenting at the Youth Health Clinics (YHC). The objectives of this study are to explore frontline healthcare provider’s perception of youth testing repeatedly for C. trachomatis as a substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…For example, a British study [ 38 ], revealed that the screening program in the UK failed to reach both young men and women engaging in risky sexual behaviour. In the same setting as the present study, health care providers described the importance of finding a balance between primary prevention (condom promotion) and secondary prevention (testing) [ 39 ], and that the encounter at the clinic facilitated finding those at risk, given that sufficient time was dedicated to each individual seeking health care.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a British study [ 38 ], revealed that the screening program in the UK failed to reach both young men and women engaging in risky sexual behaviour. In the same setting as the present study, health care providers described the importance of finding a balance between primary prevention (condom promotion) and secondary prevention (testing) [ 39 ], and that the encounter at the clinic facilitated finding those at risk, given that sufficient time was dedicated to each individual seeking health care.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that in the acculturation process, migrants could adopt a more open stance to casual sex and other sexual risk behaviours to integrate better into the new society [ 21 ]. However, these risky behaviours can be detrimental to young people´s mental health as they might worry about the negative social and health consequences of their actions, as shown in a study among youth in Sweden [ 29 ]. The cross-sectional nature of our data does not allow us to establish a temporal or causal association; however, the association between poor mental health and sexual risk behaviours must be addressed in intervention aiming to tackle poor mental health among migrants.…”
Section: Discussionmentioning
confidence: 99%
“…The interrelationship between sexual risk behaviour and mental health is complex, as one can catalyse the other [ 27 , 28 ]. For example, sexual risk behaviours in the form of unprotected sex with strangers can generate anxiety due to fears of contracting a sexually transmitted infection (STI) [ 29 ]. On the other hand, mental disorders and the medication used to treat them can increase sexual risk behaviours or impair sexual desire and people´s abilities to enjoy pleasurable sexual relations [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicated that risky sexual behaviour (e.g., condomless sexual contacts with casual partners, and higher numbers of sexual partners) were still at high levels amongst the men and at moderate levels for women in the high-risk classes (class 4 and 3, respectively). Another, more recent study in Sweden suggested that young adults might apply repeated testing as a behavioural strategy to avoid using condoms, with no corresponding change in sexual behaviour [65]. Condoms are effective in reducing the risk of chlamydia acquisition [66], and modelling studies have shown that high levels of condom use reduce chlamydia prevalence substantially [67,68].…”
Section: Discussionmentioning
confidence: 99%